Interaction of integrin αvβ3 and fibronectin under fluid shear forces: implications for tumor cell adhesion and migration - Zhuo, Paimin; Li, Quhuan; Yang, Bishan; Li, Na; Luo, Zhiqing; Zhang, Fengxia (Frontiers in Cell and Developmental Biology, 2025)
The interaction between integrin αvβ3 and fibronectin enables tumor cell adherence to endothelial layers under diverse hydrodynamic blood flow conditions, particularly in low shear stress regions. Understanding the mechanical binding characteristics between integrin αvβ3 and fibronectin under different hydrodynamic environments can provide insights into tumor cell invasion and proliferation. Here, the adhesive behavior of fibronectin-functionalized microspheres on integrin αvβ3-coated substrates under various wall fluid shear forces (0.1–0.7 dyn/cm2) was assessed using a parallel plate flow chamber system. The bond lifetimes of integrin αvβ3-fibronectin initially increased and then decreased, indicating transition from a “catch bond” to “slip bond.” Upon perfusion of fibronectin-coated microspheres into flow chambers with high-density integrin αvβ3 coating, the rolling velocity of the microspheres increased with increasing shear force. Additionally, the mean stop time and stop frequency exhibited a force-dependent biphasic pattern, initially increasing and then decreasing with shear force, demonstrating a nuanced response to mechanical forces. Thus, the integrin αvβ3–fibronectin interaction displays a “catch bond” property, influencing cell distribution in varying fluid shear forces by promoting optimal adhesion in specific shear sites. These insights enhance our understanding of tumor cell adhesion and migration in hydrodynamic environments and may aid the design of integrin αvβ3-targeted therapies.